2023
DOI: 10.1002/cncy.22682
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear membrane irregularity in high‐grade urothelial carcinoma cells can be measured by using circularity and solidity as morphometric shape definitions in digital image analysis of urinary tract cytology specimens

Abstract: Background The Paris System for Reporting Urine Cytology defines objective (elevated nuclear/cytoplasmic ratio ≥0.7) and subjective (nuclear membrane irregularity, hyperchromicity, and coarse chromatin) cytomorphologic criteria to identify conventional high‐grade urothelial carcinoma (HGUC) cells. Digital image analysis allows quantitative and objective measurement of these subjective criteria. In this study, digital image analysis was used to quantitate nuclear membrane irregularity in HGUC cells. Methods Who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 23 publications
(59 reference statements)
0
9
0
Order By: Relevance
“…The algorithm achieved an area under the receiver operating characteristic curve of 0.917 on the internal validation set, indicating a strong ability to distinguish between atypical and normal cells. Model interpretation using integrated gradients revealed that the algorithm placed a high emphasis on irregularities in the nuclear membrane as a key feature in determining cytological atypia ( Figure 2B ) 56 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The algorithm achieved an area under the receiver operating characteristic curve of 0.917 on the internal validation set, indicating a strong ability to distinguish between atypical and normal cells. Model interpretation using integrated gradients revealed that the algorithm placed a high emphasis on irregularities in the nuclear membrane as a key feature in determining cytological atypia ( Figure 2B ) 56 .…”
Section: Resultsmentioning
confidence: 99%
“…Statistical and machine learning models were implemented in Python and R 52–54 . A graphical overview is provided in Figure 1 : Slide processing– Connected components analysis to isolate individual cells and cell clusters, sped up through parallel processing 55 . Cell border detection (BorderDet)– Isolates cells within urothelial clusters with overlapping cytoplasmic borders through neural network detection model 44 . Cell-Level Measures: Morphometric measures– Additional morphological features to improve cell-type classification and atypia estimation (e.g., size / area). Urothelial Classifier (UroNet)– Used to filter urothelial cells from potentially conflated cell types through a convolutional neural network, which operates on images of cells and their morphometric measures 56 – trained on an expanded dataset with more cell classes. NC ratio estimation (UroSeg)– Estimates the NC ratio by neural network pixel-wise segmentation of background, nucleus and cytoplasm. Used as objective marker of atypia. Atypia score (AtyNet)– For predicted urothelial cells at a particular cutoff threshold, a subjective score which incorporates multiple screening criteria (e.g., hyperchromasia, etc.)…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations